2019
DOI: 10.5851/kosfa.2019.e41
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability and Quality Characteristics of Duck, Chicken, Swine and Bovine Skin Fats Extracted by Pressurized Hot Water Extraction

Abstract: The aim of this study was to investigate the oxidative status and quality characteristics of four animal skin-derived fats extracted using an identical extraction method. Pressurized hot water extraction, a green extraction method, was used to extract animal skin fats (duck, chicken, swine, and bovine skin). Multiple experiments were performed during accelerated storage at 60°C for 90 days. Quality characteristics, such as extraction yield, iodine value (IV), fatty acid composition, and fat viscosity were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Another study reports that emu oil containing a high ratio of unsaturated to saturated fatty acids protects against oxidative damage by functioning as an antioxidant or free radical scavenger, and thereby elicits hepatoprotective effects (Bennett, Code, Godin, & Cheng, ). Consistently, duck oil has a higher ratio of unsaturated to saturated fatty acids (2.26 ± 0.08) than lard oil (1.52 ± 0.01), which highlights its effective radical scavenging activity (Shin et al, ). However, the molecular mechanism(s) underlying the DO‐NE‐mediated attenuation of lipotoxicity remains unclear.…”
Section: Resultsmentioning
confidence: 84%
“…Another study reports that emu oil containing a high ratio of unsaturated to saturated fatty acids protects against oxidative damage by functioning as an antioxidant or free radical scavenger, and thereby elicits hepatoprotective effects (Bennett, Code, Godin, & Cheng, ). Consistently, duck oil has a higher ratio of unsaturated to saturated fatty acids (2.26 ± 0.08) than lard oil (1.52 ± 0.01), which highlights its effective radical scavenging activity (Shin et al, ). However, the molecular mechanism(s) underlying the DO‐NE‐mediated attenuation of lipotoxicity remains unclear.…”
Section: Resultsmentioning
confidence: 84%
“…With increasing global demand for duck meat, the production of duck has steadily increased (Kim et al, 2017 ; Shin et al, 2019 ) especially over the last 20 yr (Kim et al, 2016 ). However, this has negative implications because the disposal of by-products of duck production, including duck skin as biological waste, results in environmental pollution, which is a serious concern in the duck industry (Huda et al, 2013 ; Shim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duck oil is an avian oil that derived from duck skin, a by-product of duck meat processes (Shin et al, 2019). Recent report has shown that duck skin-derived oil contains a higher amount of long-chain fatty acids including oleic acid (18:1) and linoleic acid (18:2) than other animal skin fats, such as chicken, swine, bovine (Shin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Duck oil is an avian oil that derived from duck skin, a by-product of duck meat processes (Shin et al, 2019). Recent report has shown that duck skin-derived oil contains a higher amount of long-chain fatty acids including oleic acid (18:1) and linoleic acid (18:2) than other animal skin fats, such as chicken, swine, bovine (Shin et al, 2019). In fact, long-chain fatty acids have been shown direct beneficial effects in the prevention and treatment of many diseases, such as diabetes, obesity, and cardiovascular disorders (Fuke and Nornberg, 2017;Massaro and De Caterina, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation